Factors influencing in vitro tuberization of Chlorophytum borivilianum in solid culture - Ashraf, Mehdi Farshad; Abdul Aziz, Maheran; Abdul Kadir, Mihdzar (2012)
The present study describes an efficient technique of microtuberization of Chlorophytum borivilianum. In this study, young shoot buds of C. borivilianum were cultured on solid MS medium supplemented with 30, 60 and 90 gl-1 sucrose either individually or in combination with 0, 315, 630, 950, 1265 and 1580 μM 2-chloroethyl-trimethylammonium chloride (CCC). The highest mean number of microtubers was significantly enhanced in the presence of CCC at 950, 1265 and 1580 μM after 8 weeks of culture whereas the lowest occurred in the absence of CCC. Increasing the sucrose only stimulated microtuber elongation. The number of microtubers produced was strongly enhanced by the concentration of up to 60 gl-1 sucrose in the medium compared with 30gl-1 sucrose, but at higher level of 90 gl-1 sucrose, microtuber production declined. In the presence of sucrose, number of microtuber increased with increasing CCC level up to 1265 μM particularly at 60gl-1 with CCC mean number of microtuber per explants was more pronounced (3.5). Meanwhile, using 90gl-1 sucrose with or without CCC showed higher microtuber length which indicates that at high sucrose concentration, CCC has no significant role on tuber elongation. Results showed the most suitable combination for in vitro tuberization of C. borivilianum was 950 μM CCC with 60 gl-1 sucrose.